An SFL Analysis of Dialogues in Elementary EFL Textbooks - Niman, Erna Mena; Darong, Hieronimus Canggung (Soegijapranata Catholic University, 2024)
Textbooks play a vital role in language instruction. The study aims to examine the three metafunctions of language based on the Systemic Functional Linguistics (SFL) theory. As such, a descriptive qualitative approach along with content analysis is employed to examine dialogues that were selected conveniently from two elementary EFL textbooks. The findings indicate that the relational process is the most frequent process type indicating the ideational function of the two textbooks. For the sake of interpersonal function, declarative sentences are mostly utilized. Meanwhile, the textual function is mostly reflected by the T (Thing) and DT (Deictic + Thing) nominal group pattern. These findings have pedagogical implications for teaching English as a Foreign Language (EFL), particularly for elementary school students; providing simple language patterns that help students build a foundational vocabulary and understanding of grammar for proficient communication. The theoretical implication of the findings is the importance of scaffolded learning that helps learners grasp basic linguistic concepts before moving on to more complex and dynamic language use